Service Excellence Training for YUBASU Management In order to improve services to students - Winata, Edi (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2024)
Service Excellence Training was held with the main aim of improving the quality of service provided by the Joint Venture Foundation (YUBASU) management to the students. This training is designed comprehensively to equip administrators with the skills and knowledge needed to provide friendly, efficient and professional services. Training activities cover various important topics, including (1) effective communication, (2) time management, (3) complaint handling, (4) and developing service attitudes and ethics. The training methodology includes lectures, group discussions, case studies, and simulations, which aim to ensure participants can understand and apply the concepts taught in real situations. The expected results of this training are increasing the ability of YUBASU administrators to serve students better, creating a more conducive learning environment, as well as building harmonious relationships between administrators and students, increasing student satisfaction with the services provided and strengthening the positive image of YUBASU as an educational institution. who are committed to service quality. With this Service Excellence Training, it is hoped that YUBASU can continue to develop and make a significant contribution in producing a generation of students who are superior and have character.